Industry 4.0: Industrial Revolution of the 21st Century - Popkova, Elena G.; Ragulina, Yulia V.; Bogoviz, Aleksei V.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book addresses a wide range of issues relating to the theoretical substantiation of the necessity of Industry 4.0, the development of the methodological tools for its analysis and evaluation, and practical solutions for effectively managing this process. It particularly focuses on solving the problem of optimizing the development of Industry 4.0 in the context of knowledge economy formation. The book presents the authors' approach to studying the process of Industry 4.0 formation in connection with knowledge economy, and approach that allows the process to be studied in connection with the existing socio-economic and technological conditions. As a result, the conclusions and recommendations could be applied to modern economic systems and do not require any further elaboration. The presented research is based on modern economic theory scientific and methodological tools, including the tools of the theory of economic cycles, the theory of games, and the institutional economic theory. Raising awareness of the problem of Industry 4.0 formation, the book is of interest to a wide audience, including not only specialists and experts with a detailed knowledge of the topic, but also scholars, lecturers, and undergraduates of various fields of economics.
The Notion, Essence, and Peculiarities of Industry 4.0 as a Sphere of Industry -- Genesis of the Revolutionary Transition to Industry 4.0 in the 21st Century and Overview of Previous Industrial Revolutions -- Fundamental Differences of Transition to Industry 4.0 from Previous Industrial Revolutions -- Industry 4.0 and Closed-Loop Economy in the Context of Solving the Global Problems of Modern Times -- The Fundamental Provisions of the Concept of Knowledge Economy -- Preconditions of Formation and Development of Industry 4.0 in the Conditions of Knowledge Economy -- The Role and Importance of Knowledge Economy as a Platform for Formation of Industry 4.0 -- Methodology for Analysis and Evaluation of Industry 4.0 in the Conditions of Knowledge Economy -- Industry 4.0 as a New Vector of Growth and Development of Knowledge Economy -- Stages of Formation of Industry 4.0 and the Key Indicators of its Development -- Criteria of Evaluation of Effectiveness of Industry 4.0 from the Position of Stimulatingthe Development of Knowledge Economy -- Industry 4.0 - Transition to New Economic Reality -- Successful Experience of Formation of Industry 4.0 in Various Countries -- Causal Connections of Formation of Industry 4.0 from the Positions of the Global Economy -- Peculiarities and Problems of Formation of Industry 4.0 in Modern Russia -- Comparative Analysis of Formaion of Industry 4.0 in Developed and Developing Countries -- Priorities of Development of Industry 4.0 in Modern Economic Systems with Different Progress in Formation of Knowledge Economy -- The Mechanism of Managing the Process of Formation and Development of Industry 4.0 in Modern Economic Systems -- Modernization of the Standards of Education and Personnel Training Due to Development of Industry 4.0 in the Conditions of Knowledge Economy's Formation -- Transformation Changes in the System of Professional Competences of a Modern Specialists in the Conditions of Knowledge Economy's Formation and the Innovational Approach to Training.-The Algorithm of Managing the Process of Formation and Development of Industry 4.0 in the Modern Economic Systems in the Conditions of Knowledge Economy's Formation -- Systemic Contradictions of Modern Economic Systems that Hinder Formation and Development of Industry 4.0 in the Conditions of Knowledge Economy's Formation and Methods of Overcoming Them -- The Institutional Model of Formation and Development of Industry 4.0 in the Conditions of Knowledge Economy's Formation -- Scenarios of Development of Industry 4.0 in the Conditions of Knowledge Economy's Formation and Their Consequences for Modern Economic Systems -- Methodology of Criterial Evaluation of Consequences of The Industrial Revolution of the 21st Century -- The Approach to Managing the Development of Industry 4.0 in the Conditions of Knowledge Economy's Formation for Implementation of the Optimal Scenario.
Keywords: Computational intelligence; Industrial engineering; Production engineering; Industrial organization; Computational Intelligence; Industrial and Production Engineering; Industrial Organization